E-Courts in Indonesia: The Effectiveness of Supreme Court Regulation No. 3 of 2022 on Electronic Mediation in the Religious Courts of Medan and Riau - Putra Halomoan Hsb; Ihsan Helmi Lubis (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
This study examines the effectiveness of Supreme Court Regulation No. 3 of 2022 on electronic mediation in the Religious Courts of Medan and Riau, drawing on legal effectiveness and mediation theory. It responds to the limited comparative research on the implementation of electronic mediation across Indonesian regions, particularly in light of disparities in technological infrastructure, judicial capacity, and legal culture. The study adopts an empirical juridical approach with a qualitative design. Data were collected through interviews with mediator judges, observations of online mediation practices, and analysis of judicial documents and relevant regulations. The findings indicate that electronic mediation is a significant innovation in dispute resolution within religious courts; however, its effectiveness varies across regions. In Medan, implementation is relatively effective, supported by a more developed technological infrastructure and a stronger judicial capacity. In Riau, implementation continues to face challenges, particularly low digital literacy among disputing parties and limited access to technology. In addition, local legal culture plays a crucial role in shaping the success of mediation, especially with regard to trust in virtual communication. This study concludes that the implementation of Supreme Court Regulation No. 3 of 2022 has not yet reached full effectiveness, as alignment among legal substance, institutional structure, and legal culture remains incomplete. These findings contribute to the literature on legal effectiveness in the context of judicial digitalization and offer practical implications for strengthening judicial capacity, enhancing public digital literacy, and advancing technology-driven judicial policies.